Impressive tissue regeneration of severe oral mucositis post stem cell transplantation using cord blood platelet gel. Issue 9 (27th June 2017) - Piccin, Andrea; Rebulla, Paolo; Pupella, Simonetta; Tagnin, Mario; Marano, Giuseppe; Di Pierro, Angela Maria; Santodirocco, Michele; Di Mauro, Lazzaro; Beqiri, Lisa; Kob, Michael; Primerano, Marco; Casini, Marco; et al.
Abstract : BACKGROUND: Platelet gel from cord blood (CBPG) is a recently developed blood component for topical use. We report a case of life‐threatening mucositis after high‐dose chemotherapy with fotemustine and cytarabine that was successfully treated with CBPG. CASE REPORT: A patient with non‐Hodgkin lymphoma who was undergoing autologous hematopoietic stem cell transplantation developed severe oral and esophageal mucositis with severe bacterial sepsis and cytomegalovirus infection, causing prolonged neutropenia. CBPG was topically administered daily to the oral cavity. The CBPG was partially reabsorbed and partially swallowed. RESULTS: After 8 consecutive days of administration, the patient's oral mucosa markedly improved, showing restitutio ad integrum, and the patient's clinical status progressively improved. No side effects were seen after CBPG application. CONCLUSION: This case supports the need to conduct controlled studies comparing the efficacy of autologous and allogeneic platelet gel from adult and umbilical cord blood for the topical treatment of severe oral mucositis occurring after high‐dose chemotherapy.